EFFECTIVENESS OF STORYTELLING METHOD IN STUDENTS’ SPEAKING ABILITY - Ramadhani, Shella Fitri; Daulay, Sholihatul Hamidah; Rafida, Tien (PRIMACY Journal of English Education and Literacy, 2024)
The purpose of this research was motivated by the difficulty of students in speaking. The method used in this research is a quasi-experimental method with pre-test and post-test research design. The population of this study were eighth grade students of SMP Karyawan Turangie Langkat with sample of 27 students of class VIIIA as the experimental class and class VIIIB with 27 students as the control class. The data obtained were analyzed using normality test using Shapiro-Wilk, homogeneity test, and t-test using Independent Sample T-test using SPSS version 22 software application. The results showed there is an effect of storytelling method in speaking ability at eighth grade of SMP Karyawan Turangie Langkat, it is because the mean score in the experimental class increased significantly from 30,67 to 40,59. Meanwhile, in the control class the average value obtained also increased although not significantly from 25,19 to 28,89, and the value of Sig. 2 tailed that calculated in finding section showed 0.000 lower than alpha score 0.050 (0.000 <0.005), which means the Null Hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted.